Wet vs. dry ad libitum feeding of growing-finishing swine - David A Nichols; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1988)
Two hundred and twenty-four growing-finishing pigs were used to evaluate wet vs. dry ad libitum feeding utilizing the Pride of the Farm MaximaÂ®feeder. Growth rate, average daily feed intake, and feed/gain were the same for those pigs fed with feeders having water nozzles in the trough (wet) or (Finishing, Wet vs. Dry) without the nozzles in the trough of the feeder (dry).; Swine Day, Manhattan, KS, November 17, 1988
Keywords: Swine day; 1988; Kansas Agricultural Experiment Station contribution; no. 88-149-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 556; Swine; Finishing; Wet vs. dry